2018
DOI: 10.1089/neu.2017.5158
|View full text |Cite
|
Sign up to set email alerts
|

Acute White-Matter Abnormalities in Sports-Related Concussion: A Diffusion Tensor Imaging Study from the NCAA-DoD CARE Consortium

Abstract: Sports-related concussion (SRC) is an important public health issue. Although standardized assessment tools are useful in the clinical management of acute concussion, the underlying pathophysiology of SRC and the time course of physiological recovery after injury remain unclear. In this study, we used diffusion tensor imaging (DTI) to detect white matter alterations in football players within 48 h after SRC. As part of the NCAA-DoD CARE Consortium study of SRC, 30 American football players diagnosed with acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 83 publications
7
58
0
3
Order By: Relevance
“…However, a negative trend did exist between AD and post-concussive symptoms on the RPQ3 (which identifies somatic symptoms; i.e., headaches, dizziness, nausea), such that lower AD was associated with greater symptom presentation. This result is in line with other recent findings ( 106 ), suggesting that somatic symptom presentation may be related to axonal damage.…”
Section: Discussionsupporting
confidence: 94%
“…However, a negative trend did exist between AD and post-concussive symptoms on the RPQ3 (which identifies somatic symptoms; i.e., headaches, dizziness, nausea), such that lower AD was associated with greater symptom presentation. This result is in line with other recent findings ( 106 ), suggesting that somatic symptom presentation may be related to axonal damage.…”
Section: Discussionsupporting
confidence: 94%
“…Decreased MD has been observed by other similar studies comparing athletes to controls acutely following injury (6,8). In contrast, Mustafi et al (4) observed higher MD among acutely concussed athletes (<48 h), as compared to controls in select frontal and subfrontal white matter tracts (corpus callosum, the anterior and posterior corona radiata, and the superior longitudinal fasciculus). Elevations in MD in the bilateral longitudinal fasiculi and left corona radiata have also been observed acute among 26 recently concussed athletes (mean of 4 days since injury), as compared to matched controls (5).…”
Section: Introductionmentioning
confidence: 69%
“…A recent systematic review concluded that the physiological effects of concussion may persist beyond observed clinical recovery, typically based on self-reported symptoms, neurocognitive testing, and postural stability measures (1). Measurement of potential persistent physiological effects has largely used diffusion tensor imaging (DTI), an image technique to measure white-matter integrity derived from properties of water molecule diffusion, due to its sensitivity to detect abnormalities acutely following injury and its ability to track differences across time points in clinical recovery (1)(2)(3)(4). Specifically, differences between concussed and non-injured controls have been commonly reported for different DTI metrics, including fractional anisotropy (FA, anisotropy of water diffusion) and mean diffusivity [MD; measure of average diffusion within tissue, regardless of direction; (4-7)], acutely and throughout injury recovery.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison between measures taken 2 days and 2 weeks post‐injury in varsity contact‐sport college athletes also showed increased radial diffusivity (RD) in a cluster of right hemisphere voxels, spanning the posterior limb of the internal capsule, the retrolenticular part of the internal capsule, the inferior longitudinal fasciculus, the inferior fronto‐occipital fasciculus (sagittal stratum), and the anterior thalamic radiation (Murugavel et al, ). These findings are supported by a recent study, conducted as part of the NCAA‐DOD Care Consortium, which found that football players diagnosed with SRC displayed higher MD in frontal and subfrontal white matter (WM) fiber tracts compared to controls within 48 hr post‐injury (Mustafi et al, ). Additionally, in the concussed group, a significant positive correlation was found between axial diffusivity (AD) and clinical measures including the Brief Symptom Inventory and the Sports Concussion Assessment Tool (SCAT).…”
Section: Introductionmentioning
confidence: 61%